2021
DOI: 10.1186/s41065-020-00167-5
|View full text |Cite
|
Sign up to set email alerts
|

IFI27 may predict and evaluate the severity of respiratory syncytial virus infection in preterm infants

Abstract: Background Preterm infants are a special population that vulnerable to respiratory syncytial virus (RSV) infection and the lower respiratory tract infections (LRTIs) caused by RSV could be severe and even life-threating. The purpose of the present study was to identify candidate genes of preterm infants who are susceptible to RSV infection and provide a new insight into the pathogenesis of RSV infection. Methods Three datasets (GSE77087, GSE69606 a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…As a component of the anti-viral interferon response, it is not surprising that elevated IFI27 expression was observed in the blood of patients infected with a broad range of different respiratory viruses but not in the blood of patients with a bacterial respiratory infection. These data, combined with previous suggestions that IFI27 expression is associated with the severity of RSV ( 6 , 7 ), suggest that IFI27 may represent a pan-viral prognostic biomarker. Interestingly, when we investigated this further in the context of influenza virus, we found that expression of IFI27 L1 in the blood, rather than IFI27 itself, was associated with disease severity.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…As a component of the anti-viral interferon response, it is not surprising that elevated IFI27 expression was observed in the blood of patients infected with a broad range of different respiratory viruses but not in the blood of patients with a bacterial respiratory infection. These data, combined with previous suggestions that IFI27 expression is associated with the severity of RSV ( 6 , 7 ), suggest that IFI27 may represent a pan-viral prognostic biomarker. Interestingly, when we investigated this further in the context of influenza virus, we found that expression of IFI27 L1 in the blood, rather than IFI27 itself, was associated with disease severity.…”
Section: Discussionsupporting
confidence: 72%
“…IFI27 (also known as ISG12 or p27) is an interferon alpha (and to a lesser extent interferon gamma) inducible gene of unknown function, with the gene product residing in the nuclear membrane of the cell (5). IFI27 expression is associated with the outcomes of several different viral illnesses including respiratory syncytial virus (RSV) infection and Enterovirus 71 (EV71) hand foot and mouth disease (6,7). Preliminary evidence suggests that IFI27 expression may be a useful biomarker for COVID-19 diagnosis (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…In proteasomeassociated autoinflammatory cell models, the activation of EIF2AK2 is discovered responding to the decreased proteasome function (40). Numerous studies have demonstrated the indispensable role of IFI27 (Interferon (IFN)-a-inducible protein 27) in SLE (41)(42)(43). IFI27 is strongly correlated with the levels of T helper type 1 (Th1) cells, T helper type 2 (Th2) cells and activated dendritic cells (aDC), and the up-regulation of IFI27 is highly related to many inflammatory events induced by these immune cells (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…Viperin is also the most upregulated gene in human nasal epithelium following intranasal challenge with Rhinovirus 49 . Another RSV-related gene is I27L2 , the top upregulated gene in S. hispidus and S. fulviventer that is also the top differentially expressed gene in preterm infants with severe RSV infection 50 . Other upregulated genes also shown to be involved in RSV infection include chemokines CXCL10 51 , CXCL11 52 , LY6E 53 , MX2 54 , OAS1A 55 , ISG15 56 , IRF9 57 , NLRC5 58 and K2C6A 59 .…”
Section: Discussionmentioning
confidence: 99%